Breast tuberculosis cases rising in Sicily. (2018) - Strazzanti, Angela; Trovato, Claudio; Gangi, Santi; Basile, Francesco
Highlights: Mammary tuberculosis (TM) is an extremely rare condition. The differential diagnosis between breast cancer and breast tuberculosis is very important. It was possible to identify the Mycobacterium tuberculosis in between nucleic acid probes and PCR. Abstract: Introduction: Our work has been reported in line with the SCARE criteria [21 ]. Mammary tuberculosis (TM) is an extremely rare condition (Khanna et al., 2000 [1 ]). It has been estimated to be 0.1% of breast lesions examined histologically, but it reaches 3–4% in countries such as India and Africa where the disease shows a high incidence. This disease can present a diagnostic problem in radiological and microbiological investigations, and thus extreme caution is necessary. Presentation of case: A 26 year-old Eritrean female with a personal history of HIV infection came to our Emergency Department showing generalized limphoadenopathy and weakness in addition to a huge right breast mass. Our examination revealed a tender mass measuring 12 × 10 cm that involved all right breast. Her skin was not erythematous and local temperature was normal. She was painless. Fine needle aspiration (FNA) showed a milky and greenish shaded fluid. Conclusions: Nowadays the differential diagnosis between breast cancer and breast tuberculosis is very important, mostly in Italy and in particular in Sicily, where the massive influx of immigrants has compelled physicians to reconsider the presence of !tuberculosis.